PREVENTION OF INJURIES IN SPORTS TRAINING: AN APPROACH BASED ON PROPER LOAD AND HYGIENIC REQUIREMENTS (World Bulletin of Physical Education and Sports Science, 2025)
Preventing injuries in sports training is a critical priority to ensure the health, continued participation, and performance development of athletes at all levels. Effective prevention strategies rely on two core factors: the correct regulation of physical load and adherence to hygienic requirements. This article examines how scientifically grounded load management, combined with appropriate environmental and personal hygiene practices, can significantly reduce the risk of sports-related injuries. The study focuses on the importance of individualizing training loads based on athletes’ age, physical condition, and functional preparedness. In addition, the role of warm-up and recovery procedures, balanced nutrition, proper sports equipment, and safe training environments is analyzed. The psychological aspect of injury prevention is also discussed, emphasizing athlete awareness and coach responsibility in maintaining safety during training. Findings highlight that injuries often occur due to overload, poor technique, insufficient supervision, and neglected hygiene factors such as inadequate equipment sanitation or improper ventilation of sports facilities. Recommendations are provided to enhance injury prevention systems through professional monitoring, modern sports science methods, and systematic hygiene education for both trainers and athletes. This approach promotes long-term athletic development, reduces healthcare costs, and contributes to the formation of a safe sports culture within educational institutions.
Keywords: Sports injuries, load management, hygiene, athlete safety, prevention strategies, training process, physical education.